2022
DOI: 10.3390/genes13091632
|View full text |Cite
|
Sign up to set email alerts
|

GWAS and Transcriptome Analysis Reveal Key Genes Affecting Root Growth under Low Nitrogen Supply in Maize

Abstract: Nitrogen (N) is one of the most important factors affecting crop production. Root morphology exhibits a high degree of plasticity to nitrogen deficiency. However, the mechanisms underlying the root foraging response under low-N conditions remain poorly understood. In this study, we analyzed 213 maize inbred lines using hydroponic systems and regarding their natural variations in 22 root traits and 6 shoot traits under normal (2 mM nitrate) and low-N (0 mM nitrate) conditions. Substantial phenotypic variations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 80 publications
(104 reference statements)
0
0
0
Order By: Relevance
“…Through GWAS, 297 significant single nucleotide polymorphisms (SNPs) were detected at different N levels and 51 candidate genes with amino acid variations in coding regions or differentially expressed were identified under LN conditions. Subsequently, researchers re-sequenced the candidate gene ZmNAC36 and found that 33 variable loci in the promoter region were significantly correlated with the four root traits under LN conditions [34]. Schmidt et al identified candidate genes involved in stress signaling and hormone regulation in the MAGIC wheat population WM-800 under LN stress, such as Rht (Rht -B1 and Rht-D1) and NRT1.1 [35].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Through GWAS, 297 significant single nucleotide polymorphisms (SNPs) were detected at different N levels and 51 candidate genes with amino acid variations in coding regions or differentially expressed were identified under LN conditions. Subsequently, researchers re-sequenced the candidate gene ZmNAC36 and found that 33 variable loci in the promoter region were significantly correlated with the four root traits under LN conditions [34]. Schmidt et al identified candidate genes involved in stress signaling and hormone regulation in the MAGIC wheat population WM-800 under LN stress, such as Rht (Rht -B1 and Rht-D1) and NRT1.1 [35].…”
Section: Introductionmentioning
confidence: 99%
“…At present, the overapplication of N fertilizer in agricultural production has become a common phenomenon, but most of the current studies have been conducted under LN and normal N (NN) conditions [34,[36][37][38]. In this study, a total of 204 wheat germplasm resources were studied under three N conditions (LN, NN, and HN).…”
Section: Introductionmentioning
confidence: 99%